An unusual case of laparoscopic appendicectomy scar site endometriosis - Kala, Poomalar Gunasekaran; Elumalai, Nivetha; Sridharan, Subhasri; Arounassalame, Bupathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Scar endometriosis following caesarean section is now becoming a relatively common complication. Endometriosis in the laparoscopic port site following appendicectomy is rare. Metaplasia theory probably explains the reason behind the formation of endometriosis following a non-gynecological procedure. We reported a case of scar endometriosis in the site of laparoscopic appendicectomy scar in a 29-year-old multiparous-women, who presented with pain and swelling in the sub-umbilical area getting aggravated during menstruation. A mass of 4×3×3 cm was found extending from the subcutaneous plane to the rectus muscle in the sub-umbilical region with underlying peritoneal involvement. There was no evidence of pelvic endometriosis. As surgical treatment remains the first line in scar endometriosis with the least recurrence rate, endometrioma excision was performed with one cm margin clearance all around. As complete excision with a wide margin was done, postoperative hormone prophylaxis is not required for her. Six months follow-up did not show any recurrence.